The Macro Impact of Short‐Termism - Terry, Stephen J. (Econometrica, 2023)
R&D investment reduces current profits, so short‐term pressure to hit profit targets may distort R&D. In the data, firms just meeting Wall Street forecasts have lower R&D growth and subsequent innovation, while managers just missing receive lower pay. But short‐termist distortions might not quantitatively matter if aggregation or equilibrium dampen their impact. So I build and estimate a quantitative endogenous growth model in which short‐termism arises naturally as discipline on conflicted managers and boosts firm value by about 1%. But short‐termism reduces R&D, and the social return to R&D is higher than the private return due to standard channels including knowledge spillovers and imperfect competition. So at the macro level, short‐termist distortions slow growth by 5 basis points yearly and lower social welfare by about 1%.